Looking into the Governance of a Public Service Organization in Malta - Cacciattolo, Karen (European Scientific Journal, ESJ, 2020)
The study presented in this paper identified the type of synergy and relationship that exists between the employees and other stakeholders of a public service organization in Malta entrusted with cultural and artistic activities. Evidence was gained from indepth interviews and a total of sixty participants took part in the study, which employed a qualitative research design. A methodology based on an inductivist approach was used to explore the participants’ experiences, thoughts and opinions. Collected data, which was transcribed and converted to text, was analyzed by using the N-VIVO Qualitative Data Analysis software. In general, the governance as it stands today seems to be ‘righteous’. Employees are satisfied with their job and stakeholders are proud to be working for the organization. However, no one knows what the mission statement of the organization is or whether it exists and thus, the mission needs to be clearly and continuously communicated to all. In addition, even though everyone seems to know what the organization stands for, no one knows the exact goals and objectives, and thus, these are required to be rephrased and communicated more to all. With regards to the relationship, synergy and communication between all parties, in general it seems to be good: the weekly meetings between the management and subordinates are of benefit, and there is a cordial relationship between all parties. However, there needs to be more communication with the team of the creative director. Also, more information on the team of the creative director needs to be made visible to the Management Team and the public alike. As regards to the Board of Directors, employees and stakeholders are questioning the suitability and necessity of some of the directors acting in their own capacity since from the study it transpired that they do not seem to be contributing much.